Application of control plane technology to dynamic configurationmanagement. - McGuire, A.
The distinction between switched and leased line services is beginning to disappear. Many network operators and suppliers are developing control plane technology for application in transport networks. This will allow faster service provisioning, particularly between network operators, and the creation of new network services. However, such systems will still require comprehensive management systems, and successful operators and vendors of the future will be those that are capable of developing operational support systems that complement the control plane with service management capabilities, automated plan and build processes, inventory management, and capacity planning. This article examines the distribution of functionality between the management and central planes for support of soft permanent and switched connections
Keywords: Automated plan; Build processes; Capacity planning; Control plane technology; Dynamic configuration management; Functionality; Inventory management; Operational support systems; Service management capabilities; Service provisioning; Soft permanent connections; Switched connections; Transport networks